IMPLEMENTASI GOOD MOSQUE GOVERNANCE MELALUI PROGRAM BERSIH-BERSIH MASJID DAN PELATIHAN MANAJEMEN BKM - Fahmi Sulaiman; Henny Pratiwi; Asri Sanusi (Jurnal Pemberdayaan Sosial dan Teknologi Masyarakat, 2025)
Abstract: This Community Service Program was conducted at Al-Ikhlas Mosque, IDI Complex Medan, focusing on two major activities: a mosque cleaning program and a management capacity-building session for the Mosque Prosperity Board (BKM). The primary objective of this program was to improve the physical cleanliness and comfort of the mosque environment while simultaneously strengthening the managerial capacity of the BKM to ensure that mosque governance is implemented professionally, transparently, and sustainably. The methods employed included field observation, collective cleaning activities, lectures, group discussions, and technical assistance for BKM members. The results indicate that the cleaning activities successfully created a more hygienic, comfortable, and conducive worship environment, while also increasing community participation and awareness. The management training contributed to enhancing the BKM’s knowledge and understanding of organizational structure, role distribution, financial administration, program planning, and facility maintenance based on standard operational procedures. The program also fostered stronger collaboration between the implementing team and the local community, thus supporting the realization of good mosque governance principles. Overall, the program had a positive impact on strengthening the institutional capacity of the mosque and can serve as a replicable model for similar community service initiatives in other mosques with comparable needs. Sustainability of the program is recommended through the development of Standard Operating Procedures (SOPs) for cleanliness and administration, as well as follow-up training sessions for BKM members. Keywords: community service, mosque management, BKM, mosque cleanliness, community empowerment. Abstrak: Kegiatan Pengabdian kepada Masyarakat ini dilaksanakan di Masjid Al-Ikhlas Komplek IDI Medan dengan fokus pada dua program utama, yaitu kegiatan bersih-bersih masjid dan pemaparan manajemen Badan Kemakmuran Masjid (BKM). Program ini bertujuan untuk meningkatkan kualitas lingkungan fisik masjid sekaligus memperkuat kapasitas manajerial pengurus BKM agar tata kelola masjid dapat berjalan secara profesional, transparan, dan berkelanjutan. Metode pelaksanaan meliputi observasi lapangan, gotong royong kebersihan, ceramah, diskusi interaktif, dan pendampingan teknis kepada pengurus BKM. Hasil kegiatan menunjukkan bahwa pelaksanaan bersih-bersih masjid berhasil menciptakan lingkungan ibadah yang lebih bersih, nyaman, dan higienis, serta meningkatkan partisipasi jamaah. Sementara itu, program pemaparan manajemen memberikan peningkatan pengetahuan dan pemahaman pengurus BKM terkait struktur organisasi, pembagian tugas, administrasi keuangan, penyusunan program kerja, dan manajemen kebersihan berbasis standar operasional. Kegiatan ini juga memperkuat kolaborasi antara pihak pelaksana dan masyarakat sehingga mendorong terciptanya tata kelola masjid yang lebih baik sesuai prinsip good mosque governance. Secara keseluruhan, kegiatan ini memberikan dampak positif terhadap peningkatan kapasitas kelembagaan masjid dan dapat dijadikan model pengabdian yang dapat direplikasi di masjid lain yang memiliki kebutuhan serupa. Keberlanjutan kegiatan direkomendasikan melalui penyusunan SOP kebersihan dan administrasi serta pelatihan lanjutan bagi pengurus BKM. Kata kunci: pengabdian kepada masyarakat, manajemen masjid, BKM, kebersihan masjid, pemberdayaan masyarakat.